1999
DOI: 10.1038/sj.bjc.6690715
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of docetaxel in patients with metastatic squamous cell carcinoma of the head and neck

Abstract: -1 was found in the pharmacokinetic analysis. Docetaxel is active in this selected population with metastatic SCCHN, with a good tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 20 publications
1
38
1
3
Order By: Relevance
“…In three phase II studies (Table 1), single-agent docetaxel (100 mg m À2 ) administered on day 1 every 3 weeks produced response rates ranging from 21 to 42% (Catimel et al, 1994;Dreyfuss et al, 1996;Couteau et al, 1999). As expected, grade III -IV neutropenia was the principal toxicity in these studies.…”
Section: Potential Of Docetaxel In Scchnmentioning
confidence: 52%
See 2 more Smart Citations
“…In three phase II studies (Table 1), single-agent docetaxel (100 mg m À2 ) administered on day 1 every 3 weeks produced response rates ranging from 21 to 42% (Catimel et al, 1994;Dreyfuss et al, 1996;Couteau et al, 1999). As expected, grade III -IV neutropenia was the principal toxicity in these studies.…”
Section: Potential Of Docetaxel In Scchnmentioning
confidence: 52%
“…In the first study, TPFL-5, 23 patients with stage III -IV SCCHN received docetaxel 25 -60 mg m À2 d1 (day 1), cisplatin 25 mg m À2 d1 -5, 5-FU 700 mg m À2 (N ¼ 21) or 800 mg m À2 (N ¼ 2) d2 -5 and leucovorin 500 mg m À2 d1 -5 every 4 weeks for three cycles (Colevas et al, 1998). The ORR prior to definitive, twice daily radiation therapy was 100%, consisting of 14 Dreyfuss et al (1996) 100 mg m À2 29 42 d1 q3w Couteau et al (1999) 100 mg m À2 21 21 d1 q3w complete responses (CRs; 61%) and nine partial responses (PRs; 39%). Updated survival data (median follow-up 43 months) revealed both the 3-year overall survival and disease-free survival rates to be 78% .…”
Section: Docetaxel Plus Modified Pfl Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase II clinical trial of docetaxel monotherapy for the treatment of advanced/recurrent ESCC reported a response rate of 20.4%. These findings indicate that docetaxel may be a useful chemotherapeutic agent for the treatment of ESCC (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 78%
“…[10][11][12] Taxanes are effective and promising new agents, particularly docetaxel which has demonstrated significant single-agent activity in recurrent SCCHN. 3,13,14 Docetaxel is similar to paclitaxel with respect to its general mechanism of action (tubulin stabilization and G 2 /M cell cycle arrest), 15 however, docetaxel and paclitaxel have somewhat different pharmacodynamics and toxicities that are important in combined regimens. Recurrent or metastatic SCCHN patients treated with docetaxel-cisplatin has shown encouraging response rates and tolerability profiles which has lead to the use of docetaxel regimens as induction therapy for locally advanced disease.…”
Section: Introductionmentioning
confidence: 99%